Design of Composite Steel-Concrete Bridges using Stainless Steel Girders with Currugated Webs - Henrysson, Adam; Yman, Elly (My University, 2020)
Steel-concrete composite bridges that are designed in Sweden today are almost exclusively conducted in carbon steel. Carbon steel is susceptible to corrosion, a consequence of which is the need to maintenance, mainly in form of repainting, surveillance, and other related work, during the service life of the bridge. A reduction of the maintenance costs is possible by instead utilising stainless steel in design of the girders. Bridges in stainless steel are nearly maintenance-free and not susceptible to corrosion. However, manufacturing of bridges using stainless steel is more costly than carbon steel and therefore, effective material utilization is desirable. In this regard, beams with corrugated webs are advantageous as larger material utilization can be achieved. Girders with corrugated webs provide high shear-buckling capacity, resulting in slenderer web plates. Further, the proof stress of stainless steel is higher than that for conventional carbon steel that is often used in bridge sector. The aim of this study has been to evaluate the applicability and effectiveness of designing composite bridges by replacing carbon steel girders with flat webs, with stainless steel girders with corrugated webs. Further, the aim has been to highlight specific parameters that influence the design of such girders, and conclude the study by showing the possible savings in terms of material usage and cost estimation that could be achieved by implementing this concept. The latter is carried out by redesigning two existing composite bridges in a comparable manner to the original design. The results of the case studies show that material savings of 20-30% can be achieved by implementing the suggested concept. Furthermore, if the height of the girders were allowed to be deeper, a quadratic saving of material could be obtained for every linear increase in depth. However, there exists an optimum depth from which no excessive material savings are made by further increasing the height. The study also shows that girders designed in stainless steel are subjected to larger compressive stresses due to temperature strains. This is mainly due to the discrepancy of coefficient of thermal expansion between stainless steel and concrete. Lastly, the cost estimation analysis shows nearly the same investment costs for the original design, and the alternative with stainless steel and corrugated webs thanks to the material savings and less production costs. The cost savings over the service life of the bridge makes the investigated concept extremely beneficial. Keywords: Stainless steel, Corrugated web, Material savings, Maintenance costs, Bridge design, Steel-concrete composite bridges
Keywords: Stainless steel; Corrugated web; Material savings; Maintenance costs; Bridge design; Steel-concrete composite bridges